Relationship Between Vascular Aging and Left Ventricular Concentric Geometry in Community-Dwelling Elderly: The Northern Shanghai Study - Maimaitiaili R (Dove Medical Press, 2020)
Rusitanmujiang Maimaitiaili, Jiadela Teliewubai, Song Zhao, Jiamin Tang, Chen Chi, Yi Zhang, Yawei Xu Department of Cardiology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Yi Zhang; Yawei XuDepartment of Cardiology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, 301 Yanchang Road, Shanghai 200072, People’s Republic of ChinaTel/ Fax +86 18917686332Email yizshcn@gmail.com; xuyawei@tongji.edu.cnPurpose: There have been few recent studies regarding vascular aging and its relationship with left ventricular (LV) geometry. Moreover, the association of abnormal LV geometry with various kinds of vascular aging has not yet been systematically analyzed. Thus, this study aimed to further elucidate this relationship.Materials and Methods: In this study, 3363 older participants (43.6% male, aged 71.1± 5.9 years; 56.4% female, aged 71.1± 6.1 years) derived from the Northern Shanghai Study were enrolled. Vascular aging criteria included arteriosclerosis, defined as carotid-femoral pulse wave velocity > 10 m/s or brachial–ankle pulse wave velocity > 1800 cm/s, and peripheral atherosclerosis, defined as ankle–brachial index < 0.9, carotid artery intima-media thickness (cIMT) greater than 0.9 mm, or carotid plaque indicating carotid artery abnormality. Micro-albuminuria was defined as urinary albumin-to-creatinine ratio > 30 mg/g. Decreased estimated glomerular filtration rate (eGFR) was defined as eGFR < 60 mL/min/1.73 m2.Results: When vascular aging parameters were respectively adjusted for age and sex, arteriosclerosis, micro-albuminuria, and peripheral atherosclerosis were significantly associated with concentric remodeling, eccentric LV hypertrophy (LVH), and concentric LVH (P< 0.045) but not with decreased eGFR or abnormal cIMT and presence of plaque. Peripheral atherosclerosis was strongly associated with LV concentric geometry (LVCG) when considering other covariates (risk factors, diseases, and treatments) (P< 0.012).Conclusion: Vascular aging parameters such as arteriosclerosis, micro-albuminuria, and peripheral atherosclerosis are significantly and independently associated with LVCG in community-dwelling older Chinese population, suggesting the importance of vascular aging during early clinical assessment of abnormal LV geometry change and serious cardiovascular events.Keywords: arteriosclerosis, micro-albuminuria, peripheral atherosclerosis, community-dwelling elderly